Genetic variation of grey pomfret Pampus cinereus along the Bangladesh and Malaysia coastlines with phylogeography in the Indo-West Pacific based on mitochondrial COI and Cyt β - M.M. Mahbub Alam; Md. Moshiur Rahman; Jayed Mahbub Aomio; Nur Asma Ariffin; Mohammad Asmat-Ullah; Shamima Nasren; Sarker Mohammed Ibrahim Khalil; Md. Abdullah-Al Mamun; Muhammad Anamul Kabir; Ahasan Habib (Ecological Genetics and Genomics, 2026)

Ecological and human health risks from railway-associated contaminants: a case study of trace metal and PAH pollution along a commuter line in Chittagong, Bangladesh - Mahbub Alam; Md. Samrat Mohay Menul Islam; Muhammad Abu Bakar; Md. Ashraful Islam; Suman Das; Sreebash Chandra Bhattacharjee; Kaiser Mahmood Fahim; Md. Hasan Mahmud Babu (Environmental Geochemistry and Health, 2026)

Mitochondrial COI evidence of recent expansion and panmixia in Bangladesh Penaeus monodon, with distinct phylogeographic lineages in the Indo-Pacific - M. M. Mahbub Alam; Kristen Westfall; Snæbjörn Pálsson (Journal of Genetics, 2026)

Inverted hydrofoil energy harvesting from flow-induced pitching - Kai Qi; Md. Mahbub Alam (Ocean Engineering, 2026)

Assessing reach and perceptions of hygiene behaviour change interventions for people with disabilities and older adults: Multi-country matched cross-sectional study - Kazy Farhat Tabassum; Dewan Muhammad Shoaib; Md. Assaduzzaman Rahat; Mehedi Hasan; Dani Barrington; Ben Tidwell; Lauren D'Mello-Guyett; Anjali Sharma; Sheillah Simiyu; Ismail Hosen; Jenala Chipungu; Fachruddin Mangunjaya; et al. (International Journal of Hygiene and Environmental Health, 2026)

Assessing the Vulnerability of Sundarbans Mangroves to LST Variability: Utilising 26‐Year Spatiotemporal Data - R‐Rafiul Rahman; Md Imran Hossain Rakib; Asib Ahmed; Tahsin Tabassum; Raihan Sorker; Mahbub Alam (International Journal of Climatology, 2026)
The Sundarbans, the world's largest mangrove forest and a UNESCO World Heritage Site, is becoming increasingly susceptible to climate‐induced stress. This study examines 26 years of satellite‐derived land surface temperature (LST) data to evaluate seasonal trends, land use/land cover (LULC) changes and the spatial correlation between LST variations and predominant mangrove species in the Sundarbans of Bangladesh. LST fluctuations were most evident in the pre‐monsoon and monsoon seasons. February and December exhibited a statistically significant cooling trend over the study period. Concurrently, forest cover has decreased at an average annual rate of 5.78 km 2 , whereas coastal water bodies have increased by 5.17 km 2 , triggering microclimatic shifts that reinforce a positive feedback loop where deforestation intensifies surface heating, further accelerating forest degradation. Cluster analyses reveal sharp monthly temperature shifts outside of the pre‐monsoon season, suggesting climatic instability that could push the system toward ecological thresholds. SARIMA modelling demonstrated 95.21% accuracy in temperature forecasting for 5 years, underscoring the predictive significance of temporal analysis for future stress thresholds. Species‐specific clustering showed Ceriops decandra dominating hotter zones (26.69°C) and Heritiera fomes preferring cooler zones (25.88°C), indicating potential future redistribution or decline of sensitive species under climate extremes. This study is the first to combine species‐specific LST analysis, cluster analysis and SARIMA forecasting in the Sundarbans, offering high‐accuracy predictions of thermal stress and advancing species‐informed, adaptive management strategies.

Unveiling potential toxic metal(loid)s in popular street-vended food from a mega city (Dhaka, Bangladesh): Insights into sources, pollution status, and probabilistic risk modeling - Fizanaz Kabir; Amit Hasan Anik; Farhan Ishrak Tahmid; Md Nur E. Alam; Mahbub Alam (Food Control, 2026)

Dynamics of the energy concentration pipe in enhancing flow-induced vibration energy harvesting - Chuangye Han; Md. Mahbub Alam; Xianzong Meng; Junlei Wang (Ocean Engineering, 2026)

Antimicrobial resistance in foodborne Salmonella: Recent trends, mechanisms, and public health risks - Hrithik Roy; Rushdania Bushra; Promit Sarker; Tonni Rani Datta; Writam Saha; Farhana Binte Ferdous; Saydur Rahman; Md. Mahbub Alam (Food and Humanity, 2026)

Numerical investigation on vibration mechanisms of harbour seal whiskers in fin wakes during acceleration and cruising - Hanghao Zhao; Zhimeng Zhang; Chunning Ji; Xianghe Li; Muyuan Du; Dekui Yuan; Md Mahbub Alam (Ocean Engineering, 2026)

Numerical investigation on the vortex-induced vibration of circular cylinder based on Reynolds similarity criterion as well as vibration similarity criterion - Yingmei Li; Hongjun Zhu; Md. Mahbub Alam; Tongming Zhou (Ocean Engineering, 2026)

Vibration initiation mechanism of an inelastic cylinder in wake - Jian Liu; Md. Mahbub Alam (Ocean Engineering, 2026)

Ghrelin-disrupting activity of arsenic and its relation to cardiometabolic diseases - Kamrun Nahar Rossi; Faysal Abedin; Nayan Chandra Mohanto; Biplob Ahmed; Sobuj Mia; Nesar Uddin; Rajoana Karim Rimi; Osman Goni; Sharon Jahan Sarder; Sajib Hossain; Mainul Islam; Ahsanul Mahbub Jubayar; et al. (Toxicology and Applied Pharmacology, 2026)

Navigating Vulnerabilities and Responses for Transitioning to Viability in the Small-Scale Fisheries of Bangladesh - Mohammad Mosarof Hossain; Prateep Kumar Nayak; Md. Tariqul Alam; Md. Mostafa Shamsuzzaman; Mohammed Mahbub Iqbal; Mohammad Mahmudul Islam (Reviews in Fisheries Science & Aquaculture, 2026)

Sewer misconnection: Recommendations for increasing sewer connections in low-income urban communities in Dhaka, Bangladesh - Mahbub-Ul Alam; Md Assaduzzaman Rahat; Md Eayashen; Shahpara Nawaz; Nishantika Neeher; Kazy Farhat Tabassum; Barbara Evans; Paul Hutchings (International Journal of Hygiene and Environmental Health, 2026)

Seed Priming with Salicylic Acid Ameliorates the Salinity Induced Ionic Toxicity in Tomato (Solanum lycopersicum L.) Seedlings - Md. Shihab Uddine Khan; Shimul Mondal; Sadia Afroz Ritu; Zakaria Alam; Mahbub Ul Islam; Md. Omar Ali; Md. Motiar Rohman; Ahmed Gaber; Akbar Hossain (Journal of Plant Growth Regulation, 2026)

Crossflow-induced vibration of a near-wall cylinder behind another of smaller diameter - Guanghao Chen; Md. Mahbub Alam; Yu Zhou; Hongjun Zhu; Chunning Ji; Junlei Wang; Md Islam; Mostafa Zeinoddini (Ocean Engineering, 2025)

Trace Metal Contamination in Marine Fish Species: Implications for Food Safety and Human Health - Md. Samrat Mohay Menul Islam; Umme Hafsa Tuhin; Md. Ashraful Islam; Lutfunnesa Tamanna; Mahbub Alam; Muhammad Abu Bakar; Md. Manzoorul Kibria; Sreebash Chandra Battacherjee; Mohammad Shamsil Arafeen (Biological Trace Element Research, 2025)

Translating marine biology into engineering: A review of biomimicry and its applications - Mahadi Hasan Masud; Israt Jahan Ankhi; Abu Kaisar Md Faisal; Md. Mahbub Alam (Ocean Engineering, 2025)

Polyaromatic hydrocarbons and trace metals in road-deposited soil, source apportionment, and risk analysis: evidence from the largest port city of Bangladesh - Md. Samrat Mohay Menul Islam; Md. Nure Alam Siddik; Md. Ashraful Islam; Sharmin Ahmed Trisha; Mahbub Alam; Md. Hasan Ali; Goutam Kumar Kundu; Suman Das; Saikat Das; Md. Rezaul Karim; Dipankar Chakraborty; Sreebash Chandra Bhattacharjee; et al. (Environmental Geochemistry and Health, 2025)

A State-of-the-Art Review of the Environmental Mixtures, Exposure, and Health Risks of PFAS: A Special Focus on Developing Countries - Amit Hasan Anik; Intehum Taufique Aurnab; Maisha Binte Sultan; Md. Samium Basir; Md. Fahim Murshed; Jannatul Mustari Jarin; Raihan Sorker; Mahbub Alam; Shafi M. Tareq (Water, Air, & Soil Pollution, 2025)

Microplastics in waste management systems: An invisible threat to environmental and public health - Mohammad Toha; R-Rafiul Rahman; Mahbub Alam (Bioresource Technology Reports, 2025)

Flow-induced vibrations of a wake cylinder at a low mass-damping ratio - Jian Liu; Md. Mahbub Alam; Hongjun Zhu; Md Islam; Yu Zhou; Mostafa Zeinoddini (Ocean Engineering, 2025)

Novel evidence of arsenic-related excess adiposity and its implication in the risk of cardiometabolic diseases - Ahsanul Mahbub Jubayar; Shuchismita Khan; Junayed Sadi; Nesar Uddin; Osman Goni; Moriom Khatun; Abu Eabrahim Siddique; Ehsanul Kabir; Rajoana Karim Rimi; Sharmin Akter Beauty; Kamrun Nahar Rossi; Faysal Abedin; et al. (Environmental Research, 2025)

Unveiling the emerging concern of per- and polyfluoroalkyl substances (PFAS) and their potential impacts on estuarine ecosystems - Amit Hasan Anik; Md. Samium Basir; Maisha Binte Sultan; Mahbub Alam; Md. Mostafizur Rahman; Shafi M. Tareq (Marine Pollution Bulletin, 2025)

Mapping trace metal footprints: Distribution, sources, and risk assessment in coastal sediments near a heavy industrial zone in Bangladesh - Md. Samrat Mohay Menul Islam; Sreebash Chandra Bhattacharjee; Kaiser Mahmood Fahim; Md. Ashraful Islam; M.A.A. Shofi Uddin Sarkar; Mahbub Alam; Md. Rezaul Karim; Dipankar Chakraborty (Marine Pollution Bulletin, 2025)

Mitochondrial control region sequences show high genetic connectivity in the brownstripe snapper, Lutjanus vitta (Quoy and Gaimard, 1824) from the east coast of Peninsular Malaysia - Ahasan Habib; Nor Athirah Husna Ahmad; Nur Asma Ariffin; Ying Giat Seah; M. M. Mahbub Alam; Tun Nurul Aimi Mat Jaafar; Nur Fadli; Siti Azizah Mohd Nor; Md Moshiur Rahman (Journal of Genetics, 2024)

A comprehensive review of biofuel utilization for household cooking in developing countries: Economic and environmental impacts - Joseph O. Dirisu; Sunday O. Oyedepo; Olukunle C. Olawole; Tobiloba E. Somefun; Nkolika J. Peter; Damilola Babatunde; Collins N. Nwaokocha; Anthony O. Onokwai; Enoch Obanor; Md Mahbub Alam; Sandip A. Kale (Process Safety and Environmental Protection, 2024)

Organ-specific bioaccumulation of microplastics in market fish of Dhaka and size-dependent impacts of PVC microplastics on growth of Anabus testudineus - R-Rafiul Rahman; Abdul Baqee; Mahbub Alam; Mohammad Wahidur Khan; Md Iftakharul Muhib; Alamgir Kabir (Environmental Pollution, 2024)

Corrigendum to ‘Environmentally persistent free radicals and other paramagnetic species in wildland-urban interface fire ashes’ [Chemosphere 363 (2024) 142950] - Mahbub Alam; James Sitter; Aaron Vannucci; Jackson P. Webster; Sandrine J. Matiasek; Charles N. Alpers; Mohammed Baalousha (Chemosphere, 2024)

Environmentally persistent free radicals and other paramagnetic species in wildland-urban interface fire ashes - Mahbub Alam; James D. Sitter; Aaron K. Vannucci; Jackson P. Webster; Sandrine J. Matiasek; Charles N. Alpers; Mohammed Baalousha (Chemosphere, 2024)

Enhancing short-term vessel trajectory prediction with clustering for heterogeneous and multi-modal movement patterns - Md Mahbub Alam; Gabriel Spadon; Mohammad Etemad; Luis Torgo; Evangelos Milios (Ocean Engineering, 2024)

Flow three-dimensionality of wavy elliptic cylinder: vortex shedding bifurcation - Xiaoyu Shi; Md. Mahbub Alam; Hongjun Zhu; Chunning Ji; Honglei Bai; Mohsen Sharifpur (Ocean Engineering, 2024)

Experimental investigation on the vortex-induced vibration of a circular cylinder partially covered with moss - Hongjun Zhu; Yingmei Li; Hongtao Hao; Md. Mahbub Alam; Tongming Zhou; Tao Tang (Ocean Engineering, 2024)

Evaluation of occupational health and safety intervention for the waste and sanitation workers in Bangladesh during COVID-19 - Dewan Muhammad Shoaib; Tanvir Ahmed; Kazy Farhat Tabassum; Mehedi Hasan; Fazle Sharior; Mahbubur Rahman; Makfie Farah; Md Azizur Rahman; Alauddin Ahmed; James B. Tidwell; Mahbub-Ul Alam (International Journal of Hygiene and Environmental Health, 2024)

Machine learning-based prediction and optimization of green hydrogen production technologies from water industries for a circular economy - Mohammad Mahbub Kabir; Sujit Kumar Roy; Faisal Alam; Sang Yong Nam; Kwang Seop Im; Leonard Tijing; Ho Kyong Shon (Desalination, 2023)

FIV and energy harvesting using bluff body piezoelectric water energy harvester with different cross-sections - Yu Shen; Jiasong Wang; Md. Mahbub Alam (Ocean Engineering, 2023)

Wall-proximity effects on vortex-induced vibrations of a circular cylinder - Guanghao Chen; Md. Mahbub Alam; Yu Zhou; Chunning Ji; Hongjun Zhu (Ocean Engineering, 2023)

Receptor model-based source tracing and risk assessment of elements in sediment of a transboundary Himalayan River - Rahat Khan; Amit Hasan Anik; Shabiha Hossain; Khamphe Phoungthong; Abu Reza Md. Towfiqul Islam; Narottam Saha; Abubakr M. Idris; Md. Harunor Rashid Khan; Saad Aldawood; Mahbub Alam (Chemosphere, 2023)

Blockage effect on wakes of various bluff bodies: A review of confined flow - Ramnarayan Mondal; Md. Mahbub Alam (Ocean Engineering, 2023)

Streamwise sinusoidal flow over two identical tandem circular cylinders - Peiyuan Wang; Qiang Zhou; Md. Mahbub Alam; Yang Yang; Mingshui Li (Ocean Engineering, 2023)

Vortex-induced vibration and hydrodynamic characteristics of a round-ended cylinder - Hongjun Zhu; Bing Xu; Md Mahbub Alam; Yue Gao; Tongming Zhou (Ocean Engineering, 2023)

Biometric indices, growth pattern, and physiological status of captive-reared indigenous Yellowtail brood catfish, Pangasius pangasius (Hamilton, 1822) - Md. Arifur Rahman; Md. Rased Khan Manon; Md. Rahamat Ullah; Asraful Alam; Md. Jakiul Islam; Muhammad A. B. Siddik; Mohammed Mahbub Iqbal (Environmental Science and Pollution Research, 2023)

The impact of climate change on water resources and associated health risks in Bangladesh: A review - Amit Hasan Anik; Maisha Binte Sultan; Mahbub Alam; Fahmida Parvin; Mir Mohammad Ali; Shafi M. Tareq (Water Security, 2023)

Fluctuating forces on bluff bodies and their relationships with flow structures - Md. Mahbub Alam (Ocean Engineering, 2023)

Agro-waste-based functionalized and economic adsorbents for the effective treatment of toxic contaminants from tannery effluent - Mohammad Mahbub Kabir; Nur Nahar; Mst. Mahmoda Akter; Faisal Alam; Brandon H. Gilroyed; Marjia Mufti Misu; Md. Didar-ul-Alam; Mahmuda Hakim; Leonard Tijing; Ho Kyong Shon (Journal of Water Process Engineering, 2023)

Identification and quantification of Cr, Cu, and As incidental nanomaterials derived from CCA-treated wood in wildland-urban interface fire ashes - Mahbub Alam; Talal Alshehri; Jingjing Wang; Sheryl A. Singerling; Charles N. Alpers; Mohammed Baalousha (Journal of Hazardous Materials, 2023)

Flow structures around a circular cylinder with bilateral splitter plates and their dynamic characteristics - Hongjun Zhu; Quanyu Chen; Tao Tang; Md. Mahbub Alam; Tongming Zhou (Ocean Engineering, 2023)

Microplastics and adsorbed micropollutants as emerging contaminants in landfill: A mini review - Md. Mostafizur Rahman; Maisha Binte Sultan; Mahbub Alam (Current Opinion in Environmental Science & Health, 2023)

A review of energy extraction from wind and ocean: Technologies, merits, efficiencies, and cost - Shafiqur Rehman; Luai M. Alhems; Md. Mahbub Alam; Longjun Wang; Zakria Toor (Ocean Engineering, 2023)

Wind and wind power characteristics of the eastern and southern coastal and northern inland regions, South Africa - Shafiqur Rehman; Narayanan Natarajan; Mohamed A. Mohandes; Joshua P. Meyer; Md Mahbub Alam; Luai M. Alhems (Environmental Science and Pollution Research, 2022)

Public Health Vulnerability Due to the Exposure of Dissolved Metal(oid)s in Tap Water from a Mega City (Dhaka, Bangladesh): Source and Quality Appraisals - Shabiha Hossain; Amit Hasan Anik; Rahat Khan; Farah Tasneem Ahmed; Md. Abu Bakar Siddique; Abdul Hadi Al Nafi Khan; Narottam Saha; Abubakr M. Idris; Mahbub Alam (Exposure and Health, 2022)

Characterization of groundwater hydrogeochemistry, quality, and associated health hazards to the residents of southwestern Bangladesh - Mohammad Mahbub Kabir; Nobin Hossain; Abu Reza Md Towfiqul Islam; Samia Akter; Konica J. Fatema; Lutfun Naher Hilary; Md Hasanuzzaman; Md Didar-ul-Alam; Tasrina Rabia Choudhury (Environmental Science and Pollution Research, 2021)

Sustainable groundwater quality in southeast coastal Bangladesh: co-dispersions, sources, and probabilistic health risk assessment - Abu Reza Md. Towfiqul Islam; Mohammad Mahbub Kabir; Sharmina Faruk; Jawad Al Jahin; Md. Bodrud-Doza; Md. Didar-ul-Alam; Newaz Mohammed Bahadur; Mohammad Mohinuzzaman; Konica J. Fatema; M. Safiur Rahman; Tasrina Rabia Choudhury (Environment, Development and Sustainability, 2021)

Mitochondrial DNA variation of Metapenaeus monoceros (Decapoda, Penaeidae) reveals high genetic variation within Bangladesh with distinct lineages in the Indian Ocean - M. M. Mahbub Alam; Snæbjörn Pálsson (Marine Ecology, 2021)
The speckled shrimp Metapenaeus monoceros is a commercially important penaeid shrimp in the Indo‐West Pacific region including Bangladesh. Phylogenetics of penaeid shrimps is still a debatable issue, and molecular variation within the species is large. This study focused on the phylogeography of M. monoceros, including an assessment of the phylogenetic relationships among seven other Metapenaeus species by assessing sequence variation in three mitochondrial markers, the cytochrome oxidase subunit 1 (CO1), control region (CR) and 16S rRNA (16S). In addition, the mitochondrial variation along the Bangladesh coastline was analysed. The mitochondrial variation has a clear geographical pattern with two distinct evolutionary lineages, one found in the western Indian Ocean and the Mediterranean Sea and the second in the eastern Indian Ocean. A phylogenetic analysis of Metapenaeus based on the three markers revealed polyphyletic relationships within the genus and that the taxonomy needs revision. The mtDNA variation in Metapenaeus monoceros in Bangladesh presents a single population (AMOVA, F ST and Φ ST p > .05), which started to expand around 467 (CI: 186–753) kyr ago, and is characterized by a large number of closely related haplotypes. The study could be used to improve the management and conservation of the shrimp fishery in the region.

Decomposition of wind speed fluctuations at different time scales - Qinmin Zheng; S Rehman; Md Mahbub Alam; L M Alhems; A Lashin (Journal of Earth System Science, 2017)

Mitochondrial DNA variation reveals distinct lineages in Penaeus semisulcatus (Decapoda, Penaeidae) from the Indo‐West Pacific Ocean - M. M. Mahbub Alam; M. D. S. T. de Croos; Snæbjörn Pálsson (Marine Ecology, 2017)
Penaeus semisulcatus , the green tiger prawn, is an ecologically and economically important penaeid shrimp in the Indo‐West Pacific region, especially in rice‐shrimp farming and capture fisheries in Bangladesh and Sri Lanka, respectively. Genetic variation and phylogeography of samples of this species from Bangladesh and Sri Lanka were studied utilizing different mitochondrial DNA markers, i.e. cytochrome oxidase subunit 1 ( CO 1 ), control region ( CR ) and 16S rRNA genes. No evidence of population structure was observed in Bangladesh, but distinct variations were found among the Sri Lankan samples ( Φ ST = 0.04, p = .002; F ST = 0.07, p = .001), with the western sample differing from the northwestern and southern samples. The Bangladesh population had lower genetic diversity than two of the three Sri Lanka populations. The phylogeography of P. semisulcatus revealed two distinct mitochondrial DNA (mt DNA ) lineages, one in the Western Pacific Ocean and second in the Indian Ocean. The Bangladesh samples showed highest levels of similarity with samples from Sri Lanka, India and Malaysia, with the Bangladesh and Sri Lanka populations sharing the most common recent ancestry. Among the Indian Ocean samples, high levels of variation were observed in the samples from Iran, indicating admixture of two distinct mt DNA lineages, one shared by the populations from the Bay of Bengal and the other possibly originating from Eastern Africa. The genetic and phylogeographic information obtained in this study will be useful in appropriate planning for management and conservation of shrimp fisheries in Bangladesh and Sri Lanka, and in the Indo‐West Pacific region.

Population structure of the giant tiger shrimp Penaeus monodon in Bangladesh based on variation in microsatellites and immune-related genes - M. M. Mahbub Alam; Snæbjörn Pálsson (Marine Biology Research, 2016)

Genetic diversity of some upland and lowland rice cultivars in Bangladesh using RAPD, ISSR and SSR markers - Shah Md. Mahbub Alam; Sadia Siddika; Md. Enamul Haque; Md. Asadul Islam; Ashutosh Mukherjee; Biswanath Sikdar (The Nucleus, 2016)

Mitogenomic variation of Bangladesh Penaeus monodon (Decapoda, Panaeidae) and reassessment of its phylogeography in the Indo-West Pacific region - M. M. Mahbub Alam; Kristen M. Westfall; Snæbjörn Pálsson (Hydrobiologia, 2016)

Impact of cloud microphysics and cumulus parameterization on simulation of heavy rainfall event during 7–9 October 2007 over Bangladesh - M MAHBUB ALAM (Journal of Earth System Science, 2014)

Summer monsoon rainfall scenario over Bangladesh using a high-resolution AGCM - Md. Mizanur Rahman; M. Rafiuddin; Md. Mahbub Alam; Shoji Kusunoki; Akio Kitoh; F. Giorgi (Natural Hazards, 2013)

Seasonal forecasting of Bangladesh summer monsoon rainfall using simple multiple regression model - MD MIZANUR RAHMAN; M RAFIUDDIN; MD MAHBUB ALAM (Journal of Earth System Science, 2013)

Characterization of full-length VP4 genes of OP354-like P[8] human rotavirus strains detected in Bangladesh representing a novel P[8] subtype - Shigeo Nagashima; Nobumichi Kobayashi; Shyamal Kumar Paul; Mohammed Mahbub Alam; Mamta Chawla-Sarkar; Triveni Krishnan (Archives of Virology, 2009)

Phylogenetic analysis of rotaviruses with genotypes G1, G2, G9 and G12 in Bangladesh: evidence for a close relationship between rotaviruses from children and adults - Shyamal Kumar Paul; Nobumichi Kobayashi; Shigeo Nagashima; Masaho Ishino; Shojiro Watanabe; Mohammed Mahbub Alam; Muzahed Uddin Ahmed; Mohammad Akram Hossain; Trailokya Nath Naik (Archives of Virology, 2008)

Analysis of genetic factors related to preferential selection of the NSP1 gene segment observed in mixed infection and multiple passage of rotaviruses - M. Mahbub Alam; N. Kobayashi; M. Ishino; T. N. Naik; K. Taniguchi (Archives of Virology, 2006)

Efficiency and Flow Regime of a Highway Stormwater Detention Pond in Washington, USA - M. Akram Hossain; Mahbub Alam; David R. Yonge; Prashanta Dutta (Water, Air, & Soil Pollution, 2005)

Frequency of Bay of Bengal cyclonic storms and depressions crossing different coastal zones - Md. Mahbub Alam; Md. Arif Hossain; Sultana Shafee (International Journal of Climatology, 2003)
All the storms and depressions that formed in the Bay of Bengal during 1974–99 have been analysed. The number of occurrences in July is not in harmony with that of other months of the monsoon. Regions stricken are taken into account on a monthly, seasonal and annual basis. The Indian coast faces almost an equal number of storms and depressions that are formed from June to November. The most vulnerable months for storms are May, October and November for Bangladesh; May for Myanmar; June, August and September for Kolkata–Vishakhapatnam in India and October and November for Vishakhapatnam–Tamilnadu in India. Most of the monsoon depressions cross the Kolkata–Vishakhapatnam coast of India. The frequency of formation has been observed to decrease during the period of analysis. It is also observed that the frequency distribution of the Bay of Bengal storms has two peaks: one in the month of May and the other in the month of November. Copyright © 2003 Royal Meteorological Society